Correction: Forecasting outbound student mobility: A machine learning approach. - Stephanie Yang; Hsueh-Chih Chen; Wen-Ching Chen; Cheng-Hong Yang (PLoS ONE, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0238129.].